NOMINATIVO LATINO Y TEMA EN ESPAÑOL - Juliá, Tomás Jiménez (Collectanea philologica, 2024)
In Latin, the nominative case is usually described as Subject case, but this role is a later derivation of its function as a Theme marker. The Theme expressed by the Indo-European nominative is the syntactic Theme, not to be confused with the Theme of the FSP first described by the Prague Circle. The syntactic Theme belongs to a different and broader syntactic axis than the transitive axis. While the thematic axis divides the sentence into two parts, Theme and Predicate, the transitive axis organizes the constituents of the predicate. The syntactic Theme has several semantic features that can be found in the Theme of the so-called thematic languages. The loss of the inflectional cases in Romance languages and, therefore, of the nominative case as such, brought about the need to express the Theme analytically. This paper briefly describes the behaviour of the thematic Theme in Spanish, its relation to the transitive axis and its contrast with languages in which the thematic axis is not in force, such as English.